HEALTH EDUCATION as an EFFORTS TO PREVENT DENGUE FEVER in THE COMMUNITY of LAMKAWE VILLAGE, DARUL IMARAH DISTRICT, ACEH BESAR REGENCY in 2025 - Ramadhana, Phossy Vionica; Naimah, Naimah; Agustina, Agustina; Mairani, Tiara (Universitas Muhammadiyah Aceh, 2025)
Dengue Hemorrhagic Fever (DHF) remains a public health problem in Indonesia, including in Aceh Besar Regency, influenced by environmental factors and community behavior. Low public knowledge and awareness of DHF prevention contribute to the high risk of transmission of this disease. This community service activity aims to increase public knowledge and awareness of DHF prevention through health education. The activity was carried out in Lamkawe Village, Darul Imarah District, Aceh Besar Regency on May 22, 2025, targeting the village community, especially heads of families and adult family members. The methods used included health education accompanied by discussions and questions and answers regarding DHF and the implementation of 3M Plus behavior, evaluation through quizzes based on the material presented, and the provision of abate powder as an effort to support vector control.The abate powder was distributed through Dompet Dhuafa considering that Lamkawe Village is a fostered village. The results of the activity showed that the community gave a positive response and most participants were able to answer the quiz questions correctly, which indicates an increase in knowledge about DHF and its prevention efforts. Health education carried out in a participatory manner and supported by prevention tools has the potential to encourage changes in community behavior towards a cleaner and healthier environment as an effort to prevent dengue fever. Keywords: Health education, Dengue Hemorrhagic Fever, Abate powder